La práctica de la natación y su incidencia en el desarrollo de las habilidades y destrezas básicas, en los alumnos del 4to, 5to, 6to y 7mo año de educación básica de la escuela Mons. Jorge Guillermo Armijos Valdivieso del cantón Olmedo provincia de Loja periodo 2013-2014 - Peralta Sánchez, Diego Alberto (2014)
This research is aimed at swim practice and its impact on the development of skills and basic skills of school, "Bishop Guillermo Jorge Valdivieso Armijos " Olmedo Canton , in order to implement corrective actions , to enable stakeholders to raise awareness and raise the level of effort for improvement of this problem. The practice of swimming is not only a recreational activity but a very competitive sport recognized nationally and internationally. This research paper can be used by both parents, as teachers interested in the physical and mental health of their students and children, because the content of this thesis attached Techniques and methods that facilitated the interested reader deeper knowledge of each one of the swimming styles such as: free, backstroke, breaststroke and butterfly yet know the physical and aesthetic therapeutic benefits offered by this exciting sport. This research corresponds to an investigation of hypothetical , inferential , together with the inductive methods - deductive , Analytical - Synthetic and descriptive based on field work in the collection of empirical information on the skills and abilities in swimming was used direct observation , test , survey and interview which served to have a clear understanding about the swimming abilities and skills in each of the children have , for a study of the results presented in this way and then seek a solving the problems manifested. The direct beneficiaries are the children of the school, "Bishop Guillermo Jorge Valdivieso Armijos" and PE teacher who currently uses theoretical teaching methods that are of little interest to children at this age so incorporate methods, techniques and recreational, educational and practical activities accompanied by theoretical methods to thereby increase the interest of children and thus improve the deficiencies presented.